Types of Code-Switching in Kisah Untuk Dinda Novel - Putu Desi Anggerina Hikmaharyanti; Ni Luh Putu Eka Santiyani (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This research aimed at analyzing the code-switching used by the novelist, Erisca Febriani in her novel entitled Kisah Untuk Dinda in order to classify the types of code-switching in the form of sentence, dialogue, and narration. The method applied in this research was descriptive qualitative method. Data collection was executed by reading the novel, taking notes, and classifying the types of code-switching. The theory used in this study was proposed by Poplack as the main theory in determining the code-switching types. The result of the data analysis was presented formally and informally. In the novel, there were 135 data of code-switching divided into 3 types of code-switching, such as tag switching with 19 (14,08%) data, inter-sentential switching with 5 (3.70%) data and intra-sentential switching with 111 (82.22%) data. The most frequent type of code-switching found in the novel was intra-sentential switching, while inter-sentential switching is the least types of code switching.